Penjadwalan Perawatan dan Optimalisasi Persediaan Sparepart Mesin Press Batu Tahan Api Guna Memitigasi Akibat Breakdown pada PT XYZ - Arizqi, Moh Romadhon; Putri, Erni Puspanantasari (SURYA TEKNIKA, 2025)
PT Loka Refractories Wira Jatim is a refractory material manufacturing company for the cement, steel, power generation, and waste processing industries. In the last five months, there has been an increase in damage to the press machine, especially the stamp, disc, and moldbox components, which disrupts production and increases maintenance costs. To overcome this, the company optimizes the maintenance system and spare part management with the Total Productive Maintenance (TPM), Reliability-Centered Maintenance (RCM) and Time-Based Maintenance (TBM) approaches. MTTF and MTTR analysis are used to prepare a preventive maintenance schedule, where TBM is applied to components with predictable damage such as stamps, discs, and oil, while RCM is for gears and axles. TPM involves operators in daily maintenance. Spare part management uses the Reorder Point (ROP) method based on actual consumption and lead time, ensuring timely spare part availability without overstocking, and supporting production efficiency and sustainability.